Influence of the Bovine Leukemia Virus on the Immunological Activity by the Neutrophilic Function - Narciso, Vinícius Bigolin; Collet, Silvana Giacomini; Girardini, Lilian Kolling; Souza, Fernando Nogueira; Santa Catarina, Alcione; Della Libera, Alice Maria Melville Paiva; Sabedot, Carla; Brunetto, Thais Regina; Schneider, Marla; Blagitz, Maiara Garcia (Acta Scientiae Veterinariae, 2020)
Background: Bovine leukemia virus (VLB) is an oncogenic deltaretrovirus associated with the development of persistent lymphocytosis (LP) and lymphosarcomas in cattle. LP is characterized by chronic elevation of the number of circulating lymphocytes, in the case of B lymphocytes. Several studies have described functional changes in various leukocyte populations in both blood and milk in VLB-infected animals. The impact of some chronic diseases of low lethality is aggravated by the emergence of comorbidities.The objective of the present study was to evaluate the oxidative metabolism and neutrophil phagocytosis of bovines of the Holtein breed naturally infected with the bovine leukemia virus (VLB). Materials, Methods & Results: In this study, 20 cows were divided into three groups: (NG) seven non-seroreagent animals for VLB and without hematological alterations; (GAL) eight seroreagent animals for VLB and without hematological alterations; and (GLP) five seroreagent animals for VLB with persistent lymphocytosis (LP). The oxidative metabolism of neutrophils was determined by the tetrazolium nitroblast reduction test stimulated or not with Zymosan particles. The percentage of neutrophils that phagocytosed Zymosan particle (s) was also evaluated. The data were initially evaluated for normality and homoscedasticity by the Shapiro-Wilk test. Then the ANOVA test followed by the Student-Newman-Keuls test was applied for the comparison between the NG, GAL and GLP animals. Comparison between the NG animals and the seroreagent animals for the VLB (GVLB) was also performed through the unpaired Student’s t-test. The value of P < 0.05 was considered significant. No significant differences were observed in oxidative neutrophil metabolism in stimulated and non-stimulated samples with Zymosan particles nor in the percentage of neutrophils that phagocytosed Zymosan particle (s) among the three experimental groups. However, as no differences were observed between the seroreagent animals for VLB with and without LP, we chose to divide the animals into only two experimental, non-seroreagent and seroreagent groups for VLB. Thus, when non-seroreagent animals for the VLB were compared with the seroreagent animals for the VLB, which corresponds to the GAL and GLP animals, a significant difference was observed in relation to the oxidative metabolism by neutrophils stimulated with Zymosan particles. Discussion: Some viral diseases are often associated with increased susceptibility to new infections and several studies have evaluated the role of peripheral blood mononuclear cells in VLB infection, but few studies have investigated neutrophil function. Some authors, when evaluating phagocytic capacity and oxidative metabolism, respectively, of blood leukocytes from VLB-infected animals, observed that VLB-infected animals displaying LP had lower phagocytic capacity and lower production of Reactive Oxygen Species (ROS). Some studies have shown that oxygen consumption by neutrophils was higher in experimentally infected sheep by VLB after 15 weeks of challenge, but this species is not a natural host of the virus, since transmission does not occur between sheep and cattle and the pathogenesis of infection by VLB is more acute in sheep, a result of the lower latency period for LP development. Other authors, when evaluating the interference of VLB in milk leukocytes, concluded that VLB-infected animals show lower intensity of intracellular ROS production by flow cytometry in VLB-infected animals, especially animals expressing LP, despite the fact that percentage of milk neutrophils that produced ROS did not differ between groups. It can be concluded that VLB interferes in neutrophilic function with possible implications for the health of VLB-infected animals and may favor secondary infections.